Level practical skills of 7th grade pupils while working with technical material – metal - Ďuriš, Milan; Sojková, Mrgaréta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
At the beginning of this article we characterize the current technological education in primary schools affected by the negative impact of school reform (2008–2012). We then further describe of the methodology of field of educational research: aims, methods, hypothesis and research sample. We analyze the main research tools: non-standardized educational practical tests and observation sheets. Based on statistical processing of the student results we verify the hypothesis of the research.
Keywords: subject Technology; student; teacher; skills; wire; sheet metal; research problem; hypothesis; research analysis tools